OPTIMASI PROSES POLIMERISASI MINYAK KULIT JAMBU METE (CNSL, CASHEW NUT SHELL LIQUID) DENGAN FORMALDEHID - Luqman Buchori (Diponegoro University, 2010)
Jambu mete represents the crop which is a lot of its benefit. From various benefit of jambu mete, there is onepart of which not yet been exploited in an optimal that is husk. Whereas in its husk is contain oil so-calledCashew Nut Shell Liquid (CNSL) about 32-36%. This oil can be used as natural source phenol and alternativelysubstitution phenol from petroleum. This phenol is reacted by formaldehyde will form the phenol formaldehyderesin. Besides containing natural phenol, CNSL also contain the other bunch like karboksilat bunch, alkylbunch and alkenes bunch. This bunch will influence process of forming of phenol formaldehyde resin as aconsequence have an effect on characteristic and quality of resin so that require to be searched the optimumcondition in making of phenol formaldehyde resin. Objective of this research is to look for the optimumcondition in making of phenol formaldehyde resin of novolac type and also know the influence of comparison ofreactant and operating temperature for to resin yielded. Dependent variables in this research are reactorvolume (500 ml) with the volume bases 250 ml, catalyst acid HCl, mixing speed (200 rpm), operating time (90minute), pH (2) and operating pressure (1 atm). Independent variables are CNSL/formaldehyde ratio andoperating temperature. Perceived parameter is free rate formaldehyde. Method is used to design and processdata is RSM (Response Surface Methodology) method constructively the Static program. Result of this researchindicates that the most effect on variable is ratio CNSL/formaldehyde. Optimum condition are obtained at F/Cratio of 0.65-0.85 and temperature of 75-850C with the conversion of 0.55. The biggest rate resin obtained atF/C ratio 0.75/1 and temperature 80oC. This resin is very jell and have best sticky and also drug after runningdry. This novolac resin is applicated as furniture coating. Coating yielded have well sticky with the auburncolor.